2014
DOI: 10.4310/cms.2014.v12.n5.a7
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Wasserstein metric to seismic signals

Abstract: Seismic signals are typically compared using travel time difference or L 2 difference. We propose the Wasserstein metric as an alternative measure of fidelity or misfit in seismology. It exhibits properties from both of the traditional measures mentioned above. The numerical computation is based on the recent development of fast numerical methods for the Monge-Ampère equation and optimal transport. Applications to waveform inversion and registration are discussed and simple numerical examples are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
214
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 191 publications
(218 citation statements)
references
References 18 publications
2
214
0
2
Order By: Relevance
“…Therefore, |x−T k (x)| 2 2 + ψ(x) ∈ C 1,α is one derivative smoother than f and g (and therefore the residual). This is exactly what the preconditioning operator P (with s = −1) did to the residual in the asymptotic regime, for instance, as shown in (13). This shows that W 2 inverse matching has smoothing effect even in the non-asymptotic regime.…”
Section: Wasserstein Iterations In Non-asymptotic Regimesupporting
confidence: 73%
“…Therefore, |x−T k (x)| 2 2 + ψ(x) ∈ C 1,α is one derivative smoother than f and g (and therefore the residual). This is exactly what the preconditioning operator P (with s = −1) did to the residual in the asymptotic regime, for instance, as shown in (13). This shows that W 2 inverse matching has smoothing effect even in the non-asymptotic regime.…”
Section: Wasserstein Iterations In Non-asymptotic Regimesupporting
confidence: 73%
“…Engquist and Froese () concluded that the Wasserstein distance is insensitive to noise; a numerical example of the original data plus weak Gaussian noise is used to illustrate their conclusion. However, abnormal waveforms may occur between different seismic phases.…”
Section: Quadratic‐wasserstein‐metric‐bsed Seismic Adjoint Tomographymentioning
confidence: 97%
“…The quadratic Wasserstein, which is denoted as W 2 ( f , g ), is given as follows (Engquist & Froese, ; Villani, ): W2()f,g=infTf,gMXxTf,gx2f()xnormaldx, …”
Section: Quadratic‐wasserstein‐metric‐bsed Seismic Adjoint Tomographymentioning
confidence: 99%
See 1 more Smart Citation
“…Our work is motivated in part by [7,8,34], where the authors use the quadratic Wasserstein metric to solve Full-Waveform Inversion (FWI) problems. In particular, it is demonstrated that the quadratic Wasserstein metric, as opposed to the L 2 norm, provides an effective measure of the misfit between given data and computed solution.…”
Section: Prior Workmentioning
confidence: 99%